2020
DOI: 10.12890/2020_001710
|View full text |Cite
|
Sign up to set email alerts
|

Acalculous Acute Pancreatitis in a COVID-19 Patient

Abstract: Coronavirus disease 2019 (COVID-19) is a multisystemic condition caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with manifestations ranging from mild upper respiratory symptoms to cytokine storm causing acute respiratory distress syndrome. Pancreatic exocrine tissue and endocrine islets both express angiotensin-converting enzyme 2 (ACE2), the proven receptor for SARS-CoV-2 cell internalization. An increase in pancreatic enzymes has been increasingly recognized in patients with COVID-19,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Evidence suggests that COVID-19 produces pancreatic exocrine cell injury, resulting in pancreatitis ( 6 , 26 31 ). We observed that among pancreatic cells, ductal cells exhibited the highest levels of ACE2 and TMPRSS2 coexpression in the same cells and in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that COVID-19 produces pancreatic exocrine cell injury, resulting in pancreatitis ( 6 , 26 31 ). We observed that among pancreatic cells, ductal cells exhibited the highest levels of ACE2 and TMPRSS2 coexpression in the same cells and in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Meireles et al [ 23 ] described the case of a 36-year-old black woman with SARS-CoV-2 pneumonia, with dry cough, breathlessness, and fever for 4 d. During supplemental oxygen therapy for pneumonia, on day 7 (day 11 of disease), nausea, vomiting, and epigastric pain were reported, with no fever or other physical signs but with increased levels of amylase and lipase in blood tests. Supportive therapy was used, and clinical, laboratory, and radiological improvement was achieved (with no pancreatic pathology in CT on day 3)[ 23 ].…”
Section: Case Reports and Cohort Studies On Ap In Covid-19 In The Literature Searchmentioning
confidence: 99%
“…To the best of our knowledge, no case of necrotizing pancreatitis in the setting of COVID-19 has been reported so far. Considering the possible occurrence of mild pancreatic injury in patients with COVID-19 pneumonia, it may be prudent to evaluate pancreatic enzymes in patients presenting with GI symptoms[ 56 ]. CT imaging could be used in conjunction with the clinical parameters in order to establish a correct diagnosis or provide an alternative diagnosis when in doubt.…”
Section: Pancreatic Involvementmentioning
confidence: 99%